An investigation of the factors influencing sport tourism development - Homafar, Fazele; Honari, Habib; Heidary, Akhbar; Godarzi, Mahmud; Heidari, Taghi (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
Today,tourism and sport enjoy a complementary interrelationship directly affecting the nations` economy. Also, sport tourism is, nowadays, considered as the most profitable industry worldwide. In addition,it may affect the all social strata economically and politically.Thus needless to say that much more attention should be directed to the industry through clear-cut policies, visions and costructive plans in this regard. To this end,the present research tries to explore the ways as for sport tourism development in Iran based on the existing literatures. The data for the literature derived from certain sources like the related books,researches,articles and the figures released by world trade organization(WTO). According to the WTO,tourism industry will witness 4.1% rise by 2020 on the annual basis.Similarly,there will annually be 8.4% increase in the number of tourists travelling to Iran through 1995-2020.Currently,tourism is regarded as the main economic component worldwide involved in creating jobs and employment.